Leadership competencies for University leaders during crises - Aminudin, Rabi'ah; Jamaiudin, Norhaslinda; Abdul Razak, Dzulkifli (Akademi Kepimpinan Pendidikan Tinggi (AKEPT) and AHAS KIRKHS, 2023)
The trend in HLI leadership is characterised by the presence of leaders whose work is disconnected from the real functions of KLI which should play an important role in humanizing education. Generally, some of the leaders' focus appears to be associated with their vested interest and not giving back to the society. Some of them take the crises for granted as they view spending time in managing the situation brings no direct benefit to them. This type of transactional leadership further worsened the situation during the COVID-19 pandemic as there was always an expectation of receiving something in return for any action taken.